Hardness effects on abrasive flow machining - Gov, Kursad (Strojniški vestnik, 2013)
Abrasive flow machining (AFM) is a manufacturing technique that uses the flow of a pressurized abrasive media to remove workpiece material. In comparison with other polishing technique, AFM is very efficient, suitable for the finishing of complex inner surfaces. In this paper, the effect of workpiece hardness on the AFM process has been investigated. An experimental study was carried out on AISI D2 tool steel hardened to 31, 45 and 55 HRC. The specimens were cut by using wire electro discharge machining (WEDM) and then finished with AFM. The results show that the white layer formed during WEDM is successfully removed by AFM in a few cycles. Although the surface quality is improved by AFM for all hardness groups, the results show that harder materials have more surface improvement than the softer ones.
Keywords: abrasive flow machining; abrazivni tok; obdelava; površinska hrapavost; surface roughness; wire electro discharge machining; žična elektroerozijska obdelava